Significance and Effect of Ecological Rehabilitation Project in Inland River Basins in Northwest China - Wang, Yu (Springer US, 2013)
The Ecological Water Transfer and Rehabilitation Project in the arid inland area of northwest China is an important measure in restoring a deteriorated ecosystem. However, the sustainability of the project is affected by many socio-economic factors. This article examines the attitudes of the local populace toward the project, its impact on the livelihood of the people, and the positive effects of water-efficient agricultural practices in Ejina County. Related data were collected through questionnaire surveys and group discussions. The results identified three critical issues that may influence the sustainability of the project in the study area. The first issue relates to the impact of the project on the livelihood of local herdsmen. The potential for the sustainability of the project is compromised because the livelihood of the herdsmen greatly depends on the compensation awarded by the project. The second issue is that the project did not raise the water resource utilization ratio, which may undermine its final purpose. Finally, the compensation provided by the project considers losses in agriculture, but neglects the externalities and public benefit of eco-water. Thus, appropriate compensation mechanisms should be established and adopted according to local economic, environmental, and social conditions. Some recommendations for improving the sustainability of the project are provided based on the results of this study.